2022
DOI: 10.3390/plants11192463
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Lichens under Long-Term Passive Warming: Species-Specific Photochemical Responses to Desiccation and Heat Shock Treatments

Abstract: Climate warming in the Antarctic tundra will affect locally dominant cryptogams. Being adapted to low temperatures and freezing, little is known about the response of the polar lichens’ primary photochemistry to warming and desiccation. Since 2008, we have monitored the ecophysiological responses of lichens to the future warming scenario during a long-term warming experiment through open top chambers (OTCs) on Fildes Peninsula. We studied the primary photochemical response (potential Fv/Fm and effective effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Regarding the effect of heat stress on lichen physiological condition, many studies found that elevated temperature negatively affects the cover, diversity and photosynthetic capacity of lichens in drylands 40 , polar regions 41 , 42 and heath communities 43 . Most of them examined the effect of slightly elevated temperatures, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of heat stress on lichen physiological condition, many studies found that elevated temperature negatively affects the cover, diversity and photosynthetic capacity of lichens in drylands 40 , polar regions 41 , 42 and heath communities 43 . Most of them examined the effect of slightly elevated temperatures, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Marin et al . 42 reported that photosystem II activity persisted only up to 30 °C in four Antarctic lichen species. Our results showed that for photosynthetic apparatus in C. aculeata, the critical temperature is around 35 °C and that melanised thalli were more sensitive to heat stress.…”
Section: Discussionmentioning
confidence: 99%